2016
DOI: 10.4172/2167-0420.1000296
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Periconception Risk Factors for Adverse Pregnancy Outcomes in a Cohort of Urban Indian Women: Implications for Preconception Health Education

Abstract: Citation: Gund P, Bhide P, Kar A (2016) AbstractObjective: This study aimed at determining the prevalence of selected periconception (pre-and early-post conception) risk factors for adverse pregnancy outcomes among urban Indian women, in order to identify the targets of a preconception education programme.Methods: Data on selected risk factors for adverse pregnancy outcomes was collected through face to face interview of 2107 pregnant women. Odds ratios (OR) were computed in order to identify the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…Consanguinity: Only two studies considered consanguineous marriage as a risk factor and prevalence was 2.9 and 20% [11,18]. In a study in North Karnataka, India 26.9% of women had a history of consanguineous marriage, while the current study reported it to be 19%.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Consanguinity: Only two studies considered consanguineous marriage as a risk factor and prevalence was 2.9 and 20% [11,18]. In a study in North Karnataka, India 26.9% of women had a history of consanguineous marriage, while the current study reported it to be 19%.…”
contrasting
confidence: 54%
“…Illiteracy can be seen as a social health risk for the women, it was reported more in tribal than nontribal women (p<0.001). The other two studies also considered lower education as a risk factor [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the pregnancy cohort have been described previously [24]. There was a 9% loss to follow up as these women did not access services at the registered hospital, and could not be further contacted.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has reported the high prevalence of periconception risk factors for adverse pregnancy outcomes including birth defects among urban Indian women, especially those who were poorly educated and from low socioeconomic backgrounds [24]. In such a scenario, preconception interventions take on a very important role in the prevention of birth defects.…”
Section: Discussionmentioning
confidence: 99%